Pendekatan Multidisiplin Dalam Penanganan Anak Dengan Keterlambatan Perkembangan Di RSUD Kajen Kabupaten Pekalongan - Martin, Muhammad Arindo; adilla, amelia; Azzahra, Vevanda Musarrofah; Keniochi, Kitaro; Pratiwi, Mia Desta (Jurnal Pengabdian UntukMu NegeRI, 2026)
Children with developmental delays require comprehensive and integrated handling to support optimal growth and development. This community service activity aimed to describe the implementation of a multidisciplinary approach in handling children with developmental delays at RSUD Kajen. The method used was a descriptive qualitative approach through observation and semi-structured interviews involving psychologists, speech therapists, occupational therapists, parents, and children undergoing developmental services. The results showed that the multidisciplinary approach plays an important role in the assessment, intervention, and evaluation process through collaboration among health professionals and parents. This approach helps identify children’s developmental needs more comprehensively and supports more targeted interventions. In addition, this program produced educational media in the form of booklets, leaflets, posters, guide books, and psychoeducational videos to improve parents’ understanding of developmental stimulation and early detection. Active parental involvement also contributed positively to children’s communication, adaptive behavior, and social development. Therefore, the multidisciplinary approach needs to be continuously developed as a comprehensive service model in supporting children with developmental delays.